Calculation and Analysis of Balanced Loads in 20 kV Distribution System (Feeder 8) in Gleno Distribution Transformer - Santos, Quintão Fátima dos; Soares, Jaime Godinho; Siband, Rumbidzai Lorraine (Syntax Corporation, 2025)
This study focuses on the calculation and analysis of balanced loads in the 20 kV distribution system, specifically Feeder 8 in the Gleno Distribution Transformer, East Timor. The research aims to address the issue of load imbalance, which leads to voltage drops and power losses in the distribution network. Data were collected from eight transformers in the Gleno area, and simulations were conducted using ETAP 12.6 to analyze voltage, current, and power losses. The results indicate significant imbalances in load distribution, particularly during peak hours, resulting in neutral currents and energy losses. Recommendations are provided to improve load balancing and enhance the efficiency of the distribution system.